Characterisation of a Hydroxycinnamic Acid Esterase From the Bifidobacterium longum subsp. longum Taxon - Kelly, Sandra M.; O’Callaghan, John; Kinsella, Mike; van Sinderen, Douwe (Frontiers in Microbiology, 2018)
Bifidobacterium longum subsp. longum, a common member of the human gut microbiota with perceived positive health effects, is capable of metabolising certain complex plant carbohydrates which are typically found in the (adult) human diet. Potentially, these plant carbohydrates possibly could be employed to favourably modulate the microbial communities in the intestine. Hydroxycinnamic acids (HCAs) are plant phenolic compounds, attached to plant carbohydrates, which are associated with anti-oxidant and other beneficial properties. However, very little information is available regarding possible metabolism of HCA-containing glycans by bifidobacteria. In the current study, a gene encoding a hydroxycinnamic acid esterase was found to be conserved across the B. longum subsp. longum taxon and was present in a conserved locus associated with plant carbohydrate utilisation. The esterase was shown to be active against various HCA-containing substrates and was biochemically characterised in terms of substrate preference, and pH and temperature optima of the enzyme. Potentially, this novel hydroxycinnamic acid esterase could release HCAs from plant-based dietary sources, which may have benefits for the gut environment and thus host health.